2021
DOI: 10.1371/journal.pone.0259079
|View full text |Cite
|
Sign up to set email alerts
|

Seizure control status and associated factors among pediatric epileptic patients at a neurologic outpatient clinic in Ethiopia

Abstract: Background Childhood epilepsy is a major public health problem worldwide. Even though anti-seizure medications (ASM) have been demonstrated to control seizures, children with epilepsy continue to have frequent seizures. There is a scarcity of data on seizure control status among pediatric epileptic patients in Ethiopia. The aim of this study was to assess seizure control status and associated factors among pediatric epileptic patients. Methods A hospital based cross-sectional study was done on 261 pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Seizures were observed more frequently among children residing in urban areas (52%) compared to those in rural areas (48%). Adal et al [7] conducted a study that revealed seizures were more common in children living in urban areas than in rural ones. Asadi-Pooya and Hojabri [8] also noted that a higher proportion of people with epilepsy resided in urban (55.6%) rather than rural areas (44.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Seizures were observed more frequently among children residing in urban areas (52%) compared to those in rural areas (48%). Adal et al [7] conducted a study that revealed seizures were more common in children living in urban areas than in rural ones. Asadi-Pooya and Hojabri [8] also noted that a higher proportion of people with epilepsy resided in urban (55.6%) rather than rural areas (44.4%).…”
Section: Discussionmentioning
confidence: 99%